Radiological and Clinical Correlation of Chest X-Ray as a First Tool of Imaging in COVID-19 Patients - Talha Khalid, Farah Bano, Noreen Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: COVID-19 began to appear and spread from the city of Wuhan, China, in December 2019 around the world very quickly. Objectives: The main objective of the study is to find the radiological and clinical correlation of chest x-ray as a first tool of imaging in COVID-19 patients. Material and methods: This retrospective study was conducted in Jinnah Hospital Lahore During 2021. The data was collected from 100 COVID-19 patients. All the patients are confirmed for COVID-19 through chest X-ray (CXR). The data include all the demographic and disease profile (CBC, LFT’s, RFT’s, CXR). Results: The data was collected from 100 confirmed COVID-19 patients. There were 56 males and 44 females. The mean age was 34.56 ± 5.67 years. 46 patients were symptomatic and 54 patients were asymptomatic. Cough and fever were the most frequent symptoms. The most common co-morbidities among the patients were hypertension (15.9%) and diabetes (10.2%). Conclusion: It is concluded that chest radiograph can be used as an adjunctive prognostic indicator, in addition to other clinical information and laboratory tests, in guiding further treatment and resource allocation.